Oral mucous membrane pemphigoid in a group of Thai patients-A 15-year retrospective study - Waranun Buajeeb; Kununya Pimolbutr; Naruemon Panpradit; Nis Okuma (Elsevier, 2022)
Background/purpose: Mucous membrane pemphigoid (MMP) is a rare autoimmune disease affecting mucous membrane of the body. Oral involvement is common causing chronic and painful lesions. This study aimed to characterize oral MMP in a group of Thai patients and to analyze treatment regimens. Materials and methods: The files of patients attending Oral Medicine Clinic were retrospectively studied. Patients fulfilled diagnostic criteria of MMP were included. Chief complaints, medical and dental history, oral manifestations and investigations of individual patients were summarized. Treatment regimens and efficacy were also analyzed. Results: There were fourteen patients (age range 33-70 years) with a diagnosis of MMP. The prevalence of oral MMP was 0.51%. The lesions presented as vesicles, blood blisters, erosions, ulcers, erythema, either one type or in combination. Common complaints were chronic painful and bleeding gums. Gingival lesions were found in 13 of 14 patients (92.86%). The most common direct immunofluorescence findings were linear C3 at basement membrane zone (92.31%) followed by linear IgG deposition (84.62%). Most lesions were successfully managed with topical and/or systemic corticosteroids. The average time to control disease was 1.97 months (IQR, 0.69-12.73 months). Conclusion: Gingival lesions are very common in MMP. Mainstay of treatment is combination of systemic and topical corticosteroids. Multidisciplinary care including oral hygiene maintenance is necessary.